Analysis of Accounting Treatment of Income Based on Psak No. 72 At PT. Pegadaian Regional V Manado Office - Ummi Aiman LASALEWO; Jullie J. SONDAKH; Meily Y. B. KALALO (PT Keberlanjutan Strategis Indonesia, 2023)
Revenue is an essential component in a company's profit and loss report, which influences the company's sustainability. The greater the income earned, the more the company will profit, and vice versa. Therefore, the accounting treatment of income must be by applicable financial accounting standards to present the company's financial reports fairly and accurately. This research aims to determine how income accounting is treated based on PSAK No. 72 at PT. Pegadaian Regional Office V Manado. This type of research uses descriptive qualitative research methods. The data collection methods used in this research are interviews and documentation. The results of research that has been carried out show that the recognition, measurement, and presentation of income at PT. Pegadaian Regional Office V Manado is by PSAK No. 72; it is just that the disclosure is not entirely by PSAK No. 72 because it has yet to disclose the separation of income based on the classification of nature, amount, and time.